A boronization-induced amorphous–crystalline interface on a Prussian blue analogue for efficient and stable seawater splitting. Issue 41 (4th May 2022) - Wang, Yikang; Jia, Dongmei; Zhang, Wenyao; Jia, Gan; Xie, Haijiao; Ye, Wei; Zhu, Genping; Gao, Peng
Abstract : A durable and efficient surface-boron-rich electrocatalyst for seawater splitting was designed through a NaBH4 reduction strategy. Abstract : A promising electrocatalyst with an amorphous–crystalline structure was designed through a NaBH4 reduction strategy. Such a surface-defective heterophase structure remarkably prevents the catalyst from corroding by hindering the transport of Cl −, resulting in efficient and stable overall seawater splitting.